Effectiveness and Safety of Tranexamic Acid in Spinal Deformity Surgery - Choi, Ho Yong; Hyun, Seung-Jae; Kim, Ki-Jeong; Jahng, Tae-Ahn; Kim, Hyun-Jib (Journal of Korean Neurosurgical Society, 2017)
Spinal deformity surgery has the potential risk of massive blood loss. To reduce surgical bleeding, the use of tranexamic acid (TXA) became popular in spinal surgery, recently. The purpose of this study was to determine the effectiveness of intra-operative TXA use to reduce surgical bleeding and transfusion requirements in spinal deformity surgery. A total of 132 consecutive patients undergoing multi-level posterior spinal segmental instrumented fusion (≥5 levels) were analyzed retrospectively. Primary outcome measures included intraoperative estimated blood loss (EBL), transfusion amount and rate of transfusion. Secondary outcome measures included postoperative transfusion amount, rate of transfusion, and complications associated with TXA or allogeneic blood transfusions. The number of patients was 89 in TXA group and 43 in non-TXA group. There were no significant differences in demographic or surgical traits between the groups except hypertension. The EBL was significantly lower in TXA group than non-TXA group (841 vs. 1336 mL, =0.002). TXA group also showed less intra-operative and postoperative transfusion requirements (544 vs. 812 mL, =0.012; 193 vs. 359 mL, =0.034). Based on multiple regression analysis, TXA use could reduce surgical bleeding by 371 mL (37 % of mean EBL). Complication rate was not different between the groups. TXA use can effectively reduce the amount of intra-operative bleeding and transfusion requirements in spinal deformity surgery. Future randomized controlled study could confirm the routine use of TXA in major spinal surgery.